Developmental Venous Anomaly Presenting with Spontaneous Intracerebral Hemorrhage, Acute Ischemic Stroke, and Seizure - Mullaguri, Naresh (Cureus, 2019)
Developmental venous anomaly (DVA) is the most common, benign, congenital vascular malformation of the brain and mostly an incidental finding on imaging. The exact etiology of DVA is unknown but thought to be due to medullary vein thrombosis during embryonic venous development. DVA is generally asymptomatic although associated neurologic deficits and seizures have been described. Several reports of DVA causing neurovascular compression, obstructive hydrocephalus, venous infarction, and intracerebral hemorrhage (ICH) have been described. In this report, we discuss a patient with fluctuating neurological symptoms found to have multiple DVA, predominantly draining into the deep venous system. To the best of our knowledge, DVAs leading to simultaneous ischemic stroke, intracerebral hemorrhage, and seizures are not reported in the literature. We reviewed the relevant literature and discussed the epidemiology and clinical and radiological characteristics of DVA.